Sustainable food packaging biodegradable Carboxymethyl cellulose films reinforced with green-synthesized ZNO nanoparticles from pineapple waste - Hossain, Md. Sanower; Nur Iznin Hanis, Mohd Azhar; Nurul Aini, Mohd Azman; Jun Haslinda, Shariffuddin (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2024)
Carboxymethyl cellulose (CMC) bioplastic shows great promise for sustainable food packaging. This study synthesized zinc oxide nanoparticles (ZnO NPs) from pineapple waste via green synthesis and incorporated them into CMC to develop enhanced nanocomposite films. Key steps included preparing ZnONP powder and formulating ZnONP-CMC (ZCMC) (1.0% w/v) solutions for film fabrication. The nanocomposites were characterized using FTIR, XRD, SEM–EDX, TGA, and DSC to assess structural integrity and thermal stability. Physical properties showed enhancement, including a thickness of 0.17.05 mm, opacity of 17%, moisture content of 52.38%, and water solubility of 64.52%. The mechanical properties also improved significantly, with a tensile strength of 26.30 MPa and elongation at a break of ∼50%. FTIR and XRD confirmed the successful incorporation of ZnO NPs, which improved the crystallinity and structural integrity of the CMC matrix. Notably, the ZCMC nanocomposite exhibited rapid biodegradation within 9 days under soil conditions, highlighting its potential for reducing environmental impact. In conclusion, adding ZnO NPs to CMC films notably improves their physical, mechanical, and thermal characteristics, rendering them ideal for food packaging. While the mechanical and biodegradation properties are promising for food packaging applications, future research should focus on evaluating the antimicrobial properties and practical applications of the ZCMC films in food preservation.